2021
DOI: 10.1111/cpf.12707
|View full text |Cite
|
Sign up to set email alerts
|

The identification of biophysical parameters which reflect skin status following mechanical and chemical insults

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 35 publications
(44 reference statements)
0
15
0
Order By: Relevance
“…This might indicate that more time is required in order for this cytokine to migrate and be detectable at the skin surface. The biochemical parameters have highlighted the importance of cluster analysis, where sub‐groups within a healthy cohort respond differently to given external stimuli, as has been demonstrated by previous studies from the host laboratory 7,8 …”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…This might indicate that more time is required in order for this cytokine to migrate and be detectable at the skin surface. The biochemical parameters have highlighted the importance of cluster analysis, where sub‐groups within a healthy cohort respond differently to given external stimuli, as has been demonstrated by previous studies from the host laboratory 7,8 …”
Section: Discussionmentioning
confidence: 65%
“…This was surprising given that skin redness was visibly evident in the loaded sites of some participants, and other studies have reported significant evidence of redness following respirator application 12,25 . This may be due to the lack of sensitivity in measurement system 28,29 and its dependence on skin pigmentation 7 . The application of the Mexameter was also limited by the curved location of the nasal bridge, which could have introduced errors in the detection of erythema.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The literature reviewed emphasizes that a single parameter is not entirely sufficient to describe the skin barrier and therefore a variety of methods should be used. 46 This is also supported by a recent publication aimed to identify a set of robust parameters sensitive to mechanical and chemical challenges to skin integrity: Jayabal et al 137 attempted to use quantitative skin assessment methods to aid the early detection of skin damage for potential clinical application. They found that thresholds derived from single biophysical parameters were limited in detecting skin changes following insults.…”
Section: Discussionmentioning
confidence: 92%